Digital Promotion, Digital Payment, and Consumer Satisfaction: The Mediating Role of Perceived Ease of Use - Malwin P. Alamsyah; Adelina Lubis; Ikbar Pratama (Yayasan Sembilan Pemuda Indonesia, 2026)
This study aims to examine the effects of digital promotion and digital payment applications on consumer satisfaction by investigating the mediating role of perceived ease of use at Samudera Kuphi Coffee Shop, Medan. A quantitative explanatory approach was employed using purposive sampling, involving 98 customers who had utilized digital promotion and digital payment services. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.1.4. The findings reveal that digital promotion and digital payment applications positively and significantly influence perceived ease of use, while both variables also have significant positive effects on consumer satisfaction. In addition, perceived ease of use significantly enhances consumer satisfaction, although its mediating role in the relationship between digital promotion and consumer satisfaction was not statistically significant. Overall, the findings indicate that implementing user-friendly digital technologies can improve customer experiences and increase consumer satisfaction in the coffee shop industry. These results suggest that coffee shop managers should optimize digital promotion strategies and digital payment systems by improving application usability, transaction efficiency, and user experience to strengthen customer satisfaction. This study offers novelty by integrating digital promotion and digital payment within a single research model through the mediating role of perceived ease of use in the coffee shop context. Furthermore, it contributes to the Technology Acceptance Model (TAM) literature by providing empirical evidence that perceived ease of use is an important mechanism linking digital technologies to consumer satisfaction, while offering practical insights for businesses seeking to enhance digital service quality and customer experience.